Two Interrogated FBG Spectral Linewidth for Strain Sensing through Correlation - Shih-Hsiang Hsu; Kuo-Wei Chuang; Ci-Syu Chen; Ching-Yu Lin; Che-Chang Chang (Sensors, 2017)
The spectral linewidth from two cross-correlated fiber Bragg gratings (FBGs) are interrogated and characterized using a delayed self-homodyne method for fiber strain sensing. This approach employs a common higher frequency resolution instead of wavelength. A sensitivity and resolution of 166 MHz/με and 50 nε were demonstrated from 4 GHz spectral linewidth characterization on the electric spectrum analyzer. A 10 nε higher resolution can be expected through random noise analyses when the spectral linewidth from two FBG correlations is reduced to 1 GHz. Moreover, the FBG spectrum is broadened during strain and experimentally shows a 0.44 pm/με sensitivity, which is mainly caused by the photo elastic effect from the fiber grating period stretch.